Business Ethics as Field of Training, Teaching, and Research in East Asia - Zhou, Zucheng; Nakano, Chiaki; Luo, Ben Nanfeng (2011)
While Economic and Business Ethics has already attracted increasing attention in East Asia, a comprehensive survey of Economic and Business Ethics has never been done in this region. This study investigates the current status of Economic and Business Ethics as field of teaching, training and research in the East Asia region, particularly in China, Japan, and Korea. Based on multiple approaches that include questionnaire surveys, desktop analysis, and personal observation, this article reports on the current state of training, teaching, and research in the field of Economic and Business Ethics in the three countries. It also discusses similarities and differences with regard to these themes among the countries studied.
Keywords: Research; Teaching; Training; East Asia; Business Ethics